Tourette Syndrome Risk Genes Regulate Mitochondrial Dynamics, Structure, and Function - Clarke, Raymond A.; Furlong, Teri M.; Eapen, Valsamma (Frontiers in Psychiatry, 2021)
GGilles de la Tourette syndrome (GTS) is a neurodevelopmental disorder characterised by motor and vocal tics with an estimated prevalence of 1% in children and adolescents. GTS has high rates of inheritance with many rare mutations identified. Apart from the role of the neurexin trans-synaptic connexus (NTSC) little has been confirmed regarding the molecular basis of GTS. The NTSC pathway regulates neuronal circuitry development, synaptic connectivity and neurotransmission. In this study we integrate GTS mutations into mitochondrial pathways that also regulate neuronal circuitry development, synaptic connectivity and neurotransmission. Many deleterious mutations in GTS occur in genes with complementary and consecutive roles in mitochondrial dynamics, structure and function (MDSF) pathways. These genes include those involved in mitochondrial transport (NDE1, DISC1, OPA1), mitochondrial fusion (OPA1), fission (ADCY2, DGKB, AMPK/PKA, RCAN1, PKC), mitochondrial metabolic and bio-energetic optimization (IMMP2L, MPV17, MRPL3, MRPL44). This study is the first to develop and describe an integrated mitochondrial pathway in the pathogenesis of GTS.